Comparison of Treatment Time of Initial Alignment Between Self Ligating and Conventional System - SURESH, NILESH; KUMAR M, NAVEEN (The journal of contemporary issues in business and government, 2021)
There are various types of brackets available in orthodontics. This retrospective study investigated the difference in clinical efficiency between Damon Q self-ligating brackets (SLB) compared with MBT conventional ligating brackets (CLBs) during tooth alignment in straightwire fixed appliance therapy. Twenty patients (8 males and 12 females), aged between 12 and 25 years, were randomly divided into two groups: 9 patients received the SLB and 11 received the CLB. Upper arch impressions were taken for pre-treatment records (T0). A transpalatal arch was soldered to both maxillary first molar bands prior to extraction of the maxillary first premolars, followed by straightwire fixed appliances (0.022 × 0.028 inch). A 0.014 inch nickel titanium (NiTi) wire was used as the levelling and aligning archwire. Four monthly reviews were undertaken and impressions of the upper arch were taken at each appointment (T1, T2, T3, and T4). Displacements of the teeth were determined using Little’s irregularity index (LII). Data were analysed using the Mann–Whitney U-test. In the aligning stage, the CLB group showed significantly faster alignment of the teeth compared with the SLB group at the T1–T2 interval (P < 0.05). However, there were no differences at T2–T3, and T3–T4 for either group (P > 0.05). The CLB group showed 93 per cent crowding alleviation compared with 76 per cent for the SLB after 4 months of alignment and levelling. MBT brackets aligned the teeth faster than Damon Q but only during the first month. There was no difference in efficacy between the two groups in the later 3 weeks. Alleviation of crowding was faster with CLB than with SLB.